KONSTRUKSI SOSIAL IBU BEKERJA VS IBU RUMAH TANGGA: ANALISIS SEMIOTIKA TERHADAP IKLAN FRISIAN FLAG MAMA - Putri Limilia (SEMIOTIKA: Jurnal Komunikasi, 2016)
Mommy wars is a phenomenon that occurs in worldwide through daily conversation and digital media conversation. This phenomenon potraits the debate about ideal motherhood, where society's opinion devided into two group. First group said that full-time mother is an ideal motherhood. While another groups said that working mother is a new concept of ideal motherhood. This conception occurs whe society try to construct it through several medium. In another word, the concept of ideal motherhood is the result of social construction. Severals medium are used for mediating the process of social construction. Such as mass media. In this research, author use advertisement to clarify the social contruction of ideal motherhood. The advertisement is produced by a milk producer in Indonesia, i.e. Frisian Flag Mama. They produce an advertisement about mommy's experience in pregnancy (both working and full-time mother). Author use semiotic analysis to clarify the process of social construction, where the unit analysis are visual and text only. The research shows that this advertisement try to construct about concept of ideal motherhood within another way. They said that working mom is a modesty person, profesional, and has an equal position inside the family. Meanwhile, full-time mother is a person who has traditional taste in fashion and has lower position inside the family. The advertisement doesn't has a spesific intention to one group. Therefore, audience can have a neutral conception about ideal motherhood.Keywords: Semiotic, Advertisement, Ideal Motherhood, Social Construction.